2018
DOI: 10.1063/1.5064697
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect in thin films of the Weyl antiferromagnet Mn3Sn

Abstract: The Weyl antiferromagnet Mn3Sn has recently attracted significant attention as it exhibits various useful functions such as large anomalous Hall effect that are normally absent in antiferromagnets. Here we report the thin film fabrication of the single phase of Mn3Sn and the observation of the large anomalous Hall effect at room temperature despite its vanishingly small magnetization. Our work on the high-quality thin film growth of the Weyl antiferromagnet paves the path for developing the antiferromagnetic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 27 publications
16
86
0
Order By: Relevance
“…Figure 1c presents the X-ray diffraction (XRD) patterns of the 50-nm-thick film of Mn3+xSn1-x (x=0.02) on the SiO2 substrate obtained by the grazing angle XRD measurement. All the peaks can be indexed by the hexagonal D019 Mn3Sn structure and no additional peaks coming from plausible impurity phases are observed, which is consistent with that in the films on a thermally oxidized Si substrate 35 . Figure 1d provides a schematic diagram of our sample configuration.…”
Section: Figures 1a and 1b Show A 3d Schematic View Of Atomic Configusupporting
confidence: 81%
See 4 more Smart Citations
“…Figure 1c presents the X-ray diffraction (XRD) patterns of the 50-nm-thick film of Mn3+xSn1-x (x=0.02) on the SiO2 substrate obtained by the grazing angle XRD measurement. All the peaks can be indexed by the hexagonal D019 Mn3Sn structure and no additional peaks coming from plausible impurity phases are observed, which is consistent with that in the films on a thermally oxidized Si substrate 35 . Figure 1d provides a schematic diagram of our sample configuration.…”
Section: Figures 1a and 1b Show A 3d Schematic View Of Atomic Configusupporting
confidence: 81%
“…Figure 3e exhibits Re ( ) averaged between 2-10 meV as a function of temperature. As the temperature decreases, Re ( ) is sharply suppressed around 250 K. The similar sharp reduction of the AHE as well as magnetization has been also observed in the DC measurement 35 . Such a spin-reorientation phase transition has been studied by neutron scattering experiments, which have revealed that the 120-degree spin order in each ab plane rotates to form a helical spin ordering along the c-axis below 250 K 46 .…”
Section: Figures 3a-3d Showsupporting
confidence: 81%
See 3 more Smart Citations